The Influence of the Implementation of the Farmer Card Program and Work Motivation on the Welfare of Rice Farmers in Cilamaya Kulon, Karawang - Fajrin, Yeni (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This study aims to evaluate the implementation of the Farmer Card program and its impact on the work motivation and welfare of rice farmers in Cilamaya Kulon District, Karawang Regency. The study used a descriptive qualitative method with a literature study, and data were obtained through in-depth interviews with four informants. The results showed that most informants considered the Farmer Card program ineffective. They complained about the difficulty of obtaining subsidized fertilizer, uneven distribution, and the existence of non-farmers who misused the Farmer Card to get fertilizer and then sell it at a high price. In addition, the existence of the Farmer Card reduced farmers' work motivation due to limited access to subsidized fertilizer. This program also did not have a significant impact on farmers' welfare; high fertilizer prices due to the inaccurate distribution process became an additional burden. The informants suggested improvements to the distribution system and program implementation so that it could truly improve farmers' welfare or proposed that this program be stopped if improvements were not possible. The results showed that farmers preferred the old system which was considered more flexible in meeting fertilizer needs.